Binary Opposition and Anthropomorphism In Three Southeast Asian Folktales involving Animals - Bella Valencia Bawondes (Lingua Susastra, 2024)
In folktales, the act of labeling certain animals with certain traits is normal. However does it completely the truth? This paper then aims to examine the binary opposition and anthropomorphism within the three Asian folktales, The Quarrel of the Monkey and the Crab, The Turtle, and The Lizard,  and Sang Kancil counts The Crocodile as the characters within the story are labeled as opposite from each other and people commonly agree with that kind of labeling. In analyzing these three stories, this paper will use a qualitative method to gather the materials that are needed along with Strauss’s concept to examine the exclusive binary oppositions and their correlations with each other using syntagmatically and paradigmatically diagrams. For the anthropomorphism, it will use journals and websites that correlate with it. The result of this paper will uncover how binary oppositions and their relationship can create meaning and the possible reason why anthropomorphism happens and is often used within literature.